2022
DOI: 10.1088/1755-1315/1022/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Sago Fine Waste as a Sand Replacement Material for Cement Brick

Abstract: This paper presented a preliminary results of utilization sago fine waste as a sand replacement material for cement bricks. Sago waste is a by-product of the extraction of sago starch. Usually, the bark is not utilized for other products and being dumped directly into the rivers or left for natural degradation. About 32,250 tons of sago bark waste annually. Sand however usually obtained by using machinery at the riverbank which greatly contribute to damaging the ecosystem of the river and contributing to globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…On the other hand, lightweight bricks have numerous advantages, such as reduced structural dead load, easy to handle, lower transport costs, and lower thermal conductivity. The drastic reduction of density is similar to a preliminary study that has been conducted by I Hadi Izaan et al, [4] who reported that the replacement percentage of SFW reduced the density of the sample bricks significantly.…”
Section: Experimental Testing 321 Density Testsupporting
confidence: 87%
See 3 more Smart Citations
“…On the other hand, lightweight bricks have numerous advantages, such as reduced structural dead load, easy to handle, lower transport costs, and lower thermal conductivity. The drastic reduction of density is similar to a preliminary study that has been conducted by I Hadi Izaan et al, [4] who reported that the replacement percentage of SFW reduced the density of the sample bricks significantly.…”
Section: Experimental Testing 321 Density Testsupporting
confidence: 87%
“…It is due to the moisture content is at the optimum level and under proper curing method. The drastic reduction of strength shown above similar to a preliminary study that has been conducted by Hadi Izaan et al, [4] who reported that the replacement levels of 5% of SFW and above reduced the compressive strength of the specimens significantly. Ornam et al, [3] also reported that additional sago has reduces the strength of brick.…”
Section: Compressive Strength Testsupporting
confidence: 85%
See 2 more Smart Citations
“…When comparing both water-cement ratio values, water content with a 0.6 rate is slightly lower than water content with 0.5 percentages. Still, both absorption values are vital due to the properties of SFW, which are very absorbent materials [25].…”
Section: Water Absorption Testmentioning
confidence: 99%